The Data Visualization Tools on the Research Capability of Marketing Students - Pagaling, Ana May; Agbin, Sean Gabrielle; Bantatua, Hazel; Calzado, Remsen; De Guzman, May; Quiñones, Joyce (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the relationship between data visualization tools and the research capability of marketing students. It focused on how digital visualization tools support students’ research performance, analytical skills, digital literacy, reporting ability, collaboration, and overall research capability. No explicit theoretical framework was stated in the manuscript. The study employed a descriptive-correlational research design to describe the extent of students’ use of data visualization tools and determine their relationship with research capability without manipulating variables. The respondents were marketing students who had exposure to and experience using data visualization tools in academic and research-related activities. Data were gathered through a structured questionnaire composed of indicators on data visualization tools and research capability. Responses were rated using a Likert scale and analyzed using frequency, percentage, weighted mean, ranking, Pearson Product-Moment Correlation Coefficient, and a 0.05 level of significance. Findings showed that marketing students assessed data visualization tools positively. Software and applications received an overall weighted mean of 4.21, interpreted as Strongly Agree, while type of visualization received 4.39, also interpreted as Strongly Agree. Data analysis features received 4.60, showing that students often benefited from built-in functions, trend identification, filtering, organizing, and reporting features. Ease of use and accessibility received 3.99, while collaboration features received 3.81, both interpreted positively. In terms of research capability, students demonstrated good data analysis skills, strong reporting and presentation skills, high digital literacy and tool proficiency, and frequent use of critical thinking when working with visualized data. The results further showed that data visualization tools were effective in enhancing research capability, with the highest impact observed in research performance, level of usage, and tool features. Collaboration features showed the strongest relationship with research capability, followed by software and application and ease of use and accessibility. Type of visualization showed no significant relationship, and data analysis features had no computable correlation. The study concluded that effective utilization of data visualization tools enhances marketing students’ ability to analyze, interpret, and communicate research data. It recommended continuous student use of visualization tools, faculty integration of these tools into research activities, institutional training and software access, and a seminar-workshop on data visualization tools for enhancing research capability. The study is aligned with SDG 4 – Quality Education because it supports improved research learning, digital literacy, and academic skill development. It is also connected to SDG 9 – Industry, Innovation and Infrastructure because it promotes the use of digital tools and technology-based platforms in higher education. Its sustainability impact is mainly educational, technological, and institutional, as it supports long-term improvement in research instruction, digital competence, and technology-supported academic development.
Keywords: Data Analysis; Data Visualization Tools; Digital Literacy; Marketing Students; Research Capability; Research Performance; Visualization Tools